Karakteristik Pola Pertumbuhan Bakteri Termofilik Isolat MS-12 dari Sumber Air Padas Mudiak Sapan - Uthami, Feranis Nadia; Irdawati, Irdawati (Lembaga Yasin AlSys, 2024)
The growth pattern of thermophilic bacteria can be observed through turbidity testing, representing each growth phase: lag, exponential, stationary, and death phases. To evaluate and understand the growth pattern of thermophilic bacteria, particularly MS-12 isolate from the Mudiak Sapan (MS) hot springs, it can be analyzed through Optical Density (OD) testing using a UV-Vis spectrophotometer (600 nm). The OD test is commonly employed to determine the turbidity level in a solution by measuring the light passing through the solution, proportional to the number of cells or particles within it. The testing method used in this study is descriptive with two replications. The research was conducted at the Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, Padang State University on December 9, 2023. Bacteria were incubated for 12 hours at a temperature of 50ºC, and their growth was measured using a UV-Vis spectrophotometer with a wavelength of 600 nm. Turbidity measurements were taken every 2 hours during the 12-hour incubation period. The growth pattern of MS-12 bacterial isolate, as observed from the measurements, can be considered favorable. At the 2-hour measurement in the second hour, bacterial growth averaged at 0.1535 (lag phase). Measurements from the 3rd to the 8th hour reached an average of 0.8105 (exponential phase). The 9th and 10th hours exhibited a stationary phase, while the measurements in the last 2 hours indicated a death phase, signifying a decline in the bacterial growth pattern.